Deeper integration: What effects on trade? - Martin Clever; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
The focus of this paper is to estimate the effect of the different types of regional trade agreements on the volume of trade between country pairs. The analysis will employ the 'empirical workhorse' of international trade; the gravity model. We hypothesize that the deeper agreements have a stronger effect on trade, especially when considering the extensive margin of trade. When controlling for the extensive margin of trade, the multilateral trade resistance terms, and the endogeneity bias we are able to obtain satisfyingly accurate treatment effects of the different types of regional trade agreements. Using a panel of 50 countries over the period 1980-1999, we find that customs unions, 'deep' free trade agreements, and common markets have stronger effects on bilateral trade than simple free trade agreements.
Keywords: F1; 330; regional trade agreements; deep integration; international trade flows; gravity equation; panel data; Handelsabkommen; Handelsregionalismus; Marktintegration; Gravitationsmodell; Panel; Welt